Simultaneous Determination of Six Uncaria Alkaloids in Mouse Blood by UPLC–MS/MS and Its Application in Pharmacokinetics and Bioavailability - Chen, Lianguo (Biomed Res Int, 2020)
A specific ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method has been developed for the simultaneous determination of six Uncaria alkaloids in mouse blood with midazolam as the internal standard (IS). Only 20 μL blood was needed for sample preparation, and the protein was precipitated with acetonitrile. The UPLC BEH C18 column (2.1 mm × 100 mm, 1.7 μm) was used for chromatographic separation. The mobile phase consisted of 0.1% formic acid and acetonitrile with gradient elution within 5.5 min. Multiple reaction monitoring (MRM) and the positive electrospray ionization model were used for quantitative analysis. The accuracy of the UPLC-MS/MS method ranged from 86.5% to 110.4%. The precision for intraday and interday was ≤15% each. The mean recovery and the matrix effects were found to be 64.4-86.8% and 94.1-109.4%, respectively. The calibration curves in blood were linear in the range of 1-1000 ng/mL with a favorable correlation coefficient (r(2)) of 0.995. The pharmacokinetic results showed that six Uncaria alkaloids metabolized rapidly in mice with a half-life between 0.6 h and 4.4 h. The bioavailability of corynoxeine, isocorynoxeine, rhynchophylline, isorhynchophylline, hirsutine, and hirsuteine was 27.3%, 32.7%, 49.4%, 29.5%, 68.9%, and 51.0%, respectively, which showed satisfactory oral absorption of each alkaloid.